The indirect experience of nature: biomorphic design forms in servicescapes. Issue 6 (24th September 2020) - Kumar, Deepak S.; Purani, Keyoor; Viswanathan, Shyam A.
Abstract : Purpose: This paper aims to introduce the concept of biomorphism (i.e. indirect experience of nature) in servicescape designs and validates its impact on consumer responses. Using the stimulus-organism-response (S-O-R) framework, this study explores the relationship between biomorphic servicescape designs and the servicescape preference. Further, it explains how biomorphic designs can help users to get better connected with the servicescapes by introducing the mediating role of attention restoration and place identity (emotional and cognitive), as explained by attention restoration theory. Design/methodology/approach: Two empirical studies were carried out to test the hypothesised relationships: an exploratory pre-experimental design with one-shot treatment using 200 images as stimuli and 3, 680 responses; and a 3 × 2 factorial design with three-dimensional images with about 654 responses for three service contexts chosen a priori: fashion retail, restaurant and hospital lobby. Findings: This study conceptualises the role of biomorphism – elements that mimic natural forms – in servicescape designs and establishes that, akin to natural elements, the indirect experience of nature in servicescapes also has a positive influence on attention restoration, perceived place identity and servicescape preference of the consumers. This implies that the effects similar to that of a biophilic servicescape can be achieved through servicescape elements that mimic natural forms. Originality/value: Extending the idea of biophilia, this research adopts the concept of biomorphism from architecture and environmental psychology domains and introduces biomorphic servicescape designs, which could be more practical at times compared to biophilic servicescapes. It establishes the influences of biomorphic servicescape designs on consumer preferences. Grounded in the S-O-R model, it further explains this relationship through mediating effects of attention restoration and place identity. Being new to marketing and management domains, this research may trigger a series of research studies on biomorphic service environment designs, with desirable implications for services marketing and services operations functions.